Evaluating Cognitive Levels of Reading Comprehension Questions in Ninth Grade English Textbooks Using Revised Bloom’s Taxonomy - Arka Marlino (Publikasi Indonesia, 2025)
Reading comprehension remains a critical challenge in English as a Foreign Language (EFL) education, particularly regarding the cognitive levels of questions presented in textbooks. This study aims to evaluate the cognitive levels of reading comprehension questions in the ninth-grade English textbook